CircPrimer 2.0: a software for annotating circRNAs and predicting translation potential of circRNAs - Zhong, Shanliang; Feng, Jifeng (BMC bioinformatics, 2022)
Background Some circular RNAs (circRNAs) can be translated into functional peptides by small open reading frames (ORFs) in a cap-independent manner. Internal ribosomal entry site (IRES) and N 6 -methyladenosine (m 6 A) were reported to drive translation of circRNAs. Experimental methods confirming the presence of IRES and m 6 A site are time consuming and labor intensive. Lacking computational tools to predict ORFs, IRESs and m 6 A sites for circRNAs makes it harder. Results In this report, we present circPrimer 2.0, a Java based software for annotating circRNAs and predicting ORFs, IRESs, and m6A sites of circRNAs. circPrimer 2.0 has a graphical and a command-line interface that enables the tool to be embed into an analysis pipeline. Conclusions circprimer 2.0 is an easy-to-use software for annotating circRNAs and predicting translation potential of circRNAs, and freely available at www.bio-inf.cn .